Early Initiation of Tocilizumab Treatment Against Moderate-to-Severe Myelitis in Neuromyelitis Optica Spectrum Disorder - Du, Chen; Zeng, Pei; Han, Jin-Rui; Zhang, Tian-Xiang; Jia, Dongmei; Shi, Fu-Dong; Zhang, Chao (Frontiers in Immunology, 2021)
Background Interleukin-6 receptor blockade is effective in reducing the risk of relapses in neuromyelitis optica spectrum disorder (NMOSD). However, its efficacy during acute attacks of NMOSD remains elusive. Objective We investigated the effects of tocilizumab on disability during acute attacks, as well as its maintenance, in patients with moderate-to-severe myelitis. Methods Nineteen patients with NMOSD received tocilizumab treatment as add-on to high-dose methylprednisolone (HDMP) in acute myelitis and twenty-two patients who only received HDMP were compared. Disease disability was assessed using a multi-level scaling system that included the expanded disability status scale (EDSS), Hauser ambulation index (HAI), modified Rankin scale (mRS), pain numerical rating scale (NRS), functional assessment of chronic illness therapy-fatigue scale (FACIT-F), activity of daily living (ADL), EuroQol five-dimensions-three-level questionnaire (EQ-5D-3L), and sensory function score and bowel and bladder function score in Kurtzke functional systems scores (FSS). Results Improved EDSS, HAI, and mRS, as well as increased ADL and EQ-5D-3L were significant in patients on tocilizumab compared with those on steroids as monotherapy at 3 months (p < 0.05). Both groups of patients showed improved pain, fatigue, sensory function, and autonomic function at follow-ups, compared with baseline respectively. The changes in NRS, FACIT-F, and sensory and autonomic FSS showed no significant differences between the two groups. Tocilizumab significantly lowered the risk of relapses (HR = 0.21, 95% CI 0.06–0.76, p = 0.017) and reduced the annualized relapse rate compared with those by steroids (0.1 ± 0.2 vs 0.5 ± 0.6, p = 0.013). Conclusion Early initiation of tocilizumab provided a safe and effective add-on alternative during attacks, and its maintenance contributed to a significant reduction of relapse rate in NMOSD.